Siperiaa sanoiksi - uralilaisuutta teoiksi : Kai Donner poliittisena organisaattorina sekä tiedemiehenä antropologian näkökulmasta - Louheranta, Olavi (Helsingin yliopisto, 2010)
The doctoral dissertation, entitled Siperiaa sanoiksi - uralilaisuutta teoiksi. Kai Donner poliittisena organisaattorina sekä tiedemiehenä antropologian näkökulmasta clarifies the early history of anthropological fieldwork and research in Siberia. The object of research is Kai Donner (1888-1935), fieldworker, explorer and researcher of Finno-Ugric languages, who made two expeditions to Siberia during 1911-1913 and 1914. Donner studied in Cambridge in 1909 under the guidance of James Frazer, A. C. Haddon and W. H. R. Rivers - and with Bronislaw Malinowski. After finishing his expeditions, Donner organized the enlistment of Finnish university students to receive military training in Germany. He was exiled and participated in the struggle for Finnish independence. After that, he organized military offensives in Russia and participated in domestic politics and policy in cooperation with C. G. E. Mannerheim. He also wrote four ethnographic descriptions on Siberia and worked with the Scandinavian Arctic areas researchers and Polar explorers. The results of this analysis can be sum up as follows: In the history of ethnographic research in Finland, it is possible to find two types of fieldwork tradition. The first tradition started from M. A. Castrén's explorations and research and the second one from August Ahlqvist's. Donner can be included in the first group with Castrén and Sakari Pälsi, unlike other contemporary philologists, or cultural researcher colleagues, which used the method of August Ahlqvist. Donner's holistic, lively and participant-observation based way of work is articulated in his writings two years before Malinowski published his thesis about modern fieldwork. Unfortunately, Donner didn't get the change to continue his researche because of the civil war in Finland, and due to the dogmatic position of E. N. Setälä. Donner's main work - the ethnohistorical Siberia - encloses his political and anthropological visions about a common and threatened Uralic nation under the pressure of Russian. The important ...